Analisis Komunikasi Interpersonal Guru untuk Memotivasi Belajar Siswa Kelas V SDN Sidototo pada Era Pandemi Covid-19 Tahun Ajaran 2021/2022 - Rahmat Ardianto; Rokhmaniyah Rokhmaniyah; Ngatman Ngatman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2022)
AbstractThe motivation in learning of each student is different. It is influenced by the teacher’s interpersonal communication. The study aimed to analyze: (1) the interpersonal communication between teachers and students in motivating the learning at fifth grade of SDN Sidototo, (2) the teacher’s obstacles in motivating the learning to fifth grade students through interpersonal communication at SDN Sidototo, and (3) the teacher’s efforts to overcome the obstacles in motivating the learning to fifth grade students through interpersonal communication at SDN Sidototo. It was qualitative approach with case study method. The subject were teachers and students of fifth consisted of open-minded, empathy, encouragment, positive attitude, and equality. The student’s learning motivation implied the desire to succeed, the encouragement in learning, the hopes and dreams in the future, the appreciation in learning, the interesting activities in learning, the conducive environment in learning, and the energy to carry out learning activities. The teacher’s obstacles in motivating the learning were the students were shy to express difficulties to the teacher, the teacher’s voice was unclear for students sitting in the back row, the blackboard was bright because of the sunshine so that the students were not comfortable, the students did not pay attention when the teacher gave motivation in learning, the teacher spoke fast in providing motivation in learning to the students, all students could not use the facilities and infrastructures at the school at the same time, and the students had limited tools, limited quota, and internet network to support online learning. The teacher made appropriate efforts to overcome the obstacles.